A one-pot microwave assisted synthesis of ethyl 7,7-dimethyl-5-oxo-4-aryl-2-[(arylsulfonyl)methyl]-1,4,5,6,7,8-hexahydroquinoline-3-carboxylates under solvent-free condition and their selective cyclooxgenase (COX-1 &COX-2) inhibitor studies - P.S. HARIKRISHNAN (The Bioscan, 2025)
A four-component domino reaction of ethyl-3-oxo-4-(arylsulfonyl) butanoates, aromatic aldehydes, dimedone and ammonium acetate under microwave irradiation in solvent free condition furnished a library of novel ethyl 7,7-dimethyl-5-oxo-4-aryl-2-[(arylsulfonyl)methyl]-1,4,5,6,7,8-hexahydroquinoline-3-carboxylates. This method provides many superiority like simplicity, very high yield and environment friendly. The reaction proceed through the Hantzch condensation reaction. The synthesized compounds were subjected to selective cyclooxygenase (COX-1 & COX-2) inhibitor evaluation studies.